A retrospective comparative study on the treatment of non-metastatic pancreatic cancer using high-intensity focused ultrasound versus radical surgery - Li Yu; Yunfei Liu; Zhiqiang Li; Yanyan Huang; Guangping Tu; Qiuling Shi; Lang Chen; Xiao Yu (International Journal of Hyperthermia)
Objective To compare the efficacy and safety of high-intensity focused ultrasound (HIFU) and radical surgery for non-metastatic pancreatic cancer (PC).Materials and methods We retrospectively analyzed 89 stage I/II/III PC patients who underwent HIFU (n = 43) or surgery (n = 46) at the Third Xiangya Hospital from January 2020 to December 2021. Pain relief, Karnofsky Performance Scale (KPS), overall survival (OS), treatment-related complications and risk factors for OS were assessed.Results There was no significant difference in the pain relief rate at 30 days post-treatment between the two groups. However, compared with the surgery group, the HIFU group showed significantly lower post-treatment VAS scores (p = 0.019). In the surgery group, the KPS at 30 days post-treatment was lower than pretreatment KPS (70 vs 80; p = 0.015). This relationship was reversed in the HIFU group (80 vs 70; p = 0.024). Median OS favored surgery over HIFU (23 vs 10 months; p < 0.001), with a higher 1-year OS rate (69.57% vs 32.6%; p < 0.001). However, there was no significant difference in OS between the two groups for stage III patients (p = 0.177). Complications rated ≥ grade III were 2.33% in the HIFU group and 32.6% in the surgery group. Multivariate analyses showed that age, KPS, and treatment methods were independent prognostic factors for OS.Conclusion HIFU demonstrates advantages over surgery in terms of early KPS, VAS improvements, and safety for pancreatic cancer; however, long-term outcomes favor surgery. For III-stage disease, HIFU was noninferior to surgery in overall survival.